Benchmarking AI and human text classifications in the context of newspaper frames: A multi-label LLM classification approach - Alexander Tripp (Research & Politics)
I examine the abilities of large language models (LLMs) to accurately classify topics related to immigration from Spanish-language newspaper articles. I benchmark various LLMs (ChatGPT and Claude) and undergraduate coders with my own codings. I prompt models to label articles with either an 8 label scheme—directly analogous to the assignment of the undergraduate coders—or a 4 label scheme—aggregating the 8 labels into broader themes. In my analyses, a Few Shot ChatGPT 4o model with 8 labels emerges as the most reliable LLM classifier and comes close to the undergraduate coders, with models using 8 labels generally outperforming their 4 label counterparts. I also find that LLMs tend toward false positive errors. This application provides practical methodological guidance for applied researchers using LLMs in data coding. Overall, I demonstrate how LLMs can be effective supplements to human coders, as well as the continued value of human coding as a benchmark for text classification.